Identificação molecular, susceptibilidade aos antifúngicos e inibição fotodinâmica antimicrobiana no gênero Malassezia - Diogo Coelho de Padua Oliveira (2014)
The genus Malassezia clustering 14 species of lipophilic and/or lipodependent yeasts present in human and animals indigenous microbiota. The genus is involved in the pathogenesis of pityriasis versicolor, seborrheic dermatitis and otitis, this occurring in animals. Conventional treatment of malassezioses is based on antifungals although recurrences are frequent. Antimicrobial photodynamic inhibition (aPDI) has been showning potential to support viable therapeutic alternatives. In the present work, it was carried out the specific molecular identification of Malassezia samples (41 samples from humans and 10 from dogs), the determination of minimum inhibitory concentration (MIC) of six antifungals (caspofungin, ketoconazole, clotrimazole, isoconazole, itraconazole, miconazole) and the application of aIFD employing two photoabsorvers (orthotoulidine blue and C substance) and light sources emitting at 630nm (red) and 430nm (blue). Previous attempts of grouping the samples based on genetic similarity by PCR fingerprinting with primer (GTG)5 were ineffective for species typing. Subsequently, 34 samples were identified by sequencing employing the primers NL1/NL4 from the D1/D2 region of the ribosomal gene. Sequencing revealed seven species: M. furfur, M. globosa, M. pachydermatis, M. slooffiae, M. sympodialis, M. yamatoensis and M. japonica. This is the first description of the occurrence of the latter two species in Latin America. The results of MIC determination showed high values (> 16 mg/mL) for caspofungina, suggestive of natural resistence. The MIC50 and MIC90 values obtained for the other drugs were generally higher than those reported in literature for species of Malassezia spp. To M. furfur, these values (MIC50 and MIC90) were ketoconazole 0.25 and 2 g/mL; isoconazole 4 and 16 g/mL; itraconazole - 0.125 and 8 g/mL; for clotrimazole and miconazole the same values were obtained of 2 and 16 g/mL. For the genus Malassezia, these were the MIC50 and MIC90 values determined: ketoconazole - 1 and 16 g/mL; isoconazole 8 and 16 g/mL, itraconazole - 0.125 and 16 g/mL, clotrimazole - 8 g/mL and 64 g/mL; miconazole - 4 g/mL and 16 g/mL. The calculation of the molar equivalence of the tested drugs indicated itraconazole as the most efficient drug. In the aIFD models with the red light and blue light allowed the reduction of Malassezia cell viability of 1.4 log10 CFU/mL and 1.7 log10 CFU/ mL, respectively